2017
DOI: 10.1111/bjh.14606
|View full text |Cite
|
Sign up to set email alerts
|

A clinical review of communication training for haematologists and haemato‐oncologists: a case of art versus science

Abstract: The art of communication at times seems at odds with the science of medicine. Poor communication is associated with risks for patient and physician. Communication skills are highly relevant for haematologists and are associated with increased physician and patient satisfaction, positive psychosocial outcomes and possible health outcomes. Medical communication training has recently become widespread but is largely restricted to junior medical professionals. In haematology, the proliferation of high quality comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…As far as we know, few training courses in communication are addressed to haematologists and thus focus on their specific communication needs [63]. At the same time, communication remains a challenge for haematologists.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, few training courses in communication are addressed to haematologists and thus focus on their specific communication needs [63]. At the same time, communication remains a challenge for haematologists.…”
Section: Discussionmentioning
confidence: 99%
“…Our study interviewees also reported variation in haematologists' confidence in commencing ‘difficult’ discussions. A recent UK review reports varying levels of satisfaction among haemato-oncologists with their communication skills training and little evidence of consistency in teaching beyond medical school and specialist training (Christie and Glew, 2017). Such interventions are recommended, however, if the communication challenges faced by haematologists are to be met (Dharmarajan et al, 2016; Odejide et al, 2016; Christie and Glew, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As reported by previous studies, today's socio-cultural expectations require physicians to understand patients' feelings and show empathy [24]. This issue would be a challenge for physicians believing that they should maintain a professional distance with their patients in terms of emotions [25].…”
Section: Discussionmentioning
confidence: 99%